(untitled) (Journal of Pharmaceutical Negative Results, 2022)
Background: Globally maximum student are using smartphone and it’s popular to use it. Smartphone addiction will give wrong impact on their life. Few previously conducted researches say that smartphone addiction can have effect on academics, psychology, physiology etc.Objective: Present study is having objective of assessing smartphone addiction among undergraduate students.Methodology: Research design used for study was cross sectional research design. 100 samples were selected by non-probability convenient sampling method from undergraduates nursing students of Krishna Institute of Nursing Sciences, Karad to identify smartphone addiction among undergraduate nursing student which was assessed by smartphone addiction scale and calculated by descriptive and inferential statistic. Result: 1(1%) sample is severely addicted, 23(23%) sample were mildly addicted and 76(76%) sample is moderately addicted.bConclusion: Research finding revels that undergraduate are moderately addicted to smartphone and some planning with implementation should done to have result of smartphone deaddiction.